Firm entry and institutional lock-in: an organizational ecology analysis of the global fashion design industry - Rik Wenting; Koen Frenken (Max Planck Institute of Economics, 2007)
Few industries are more concentrated than the global fashion industry. We analyse the geography and evolution of the ready-to-wear fashion design industry by looking at the yearly entry rates following an organizational ecology approach. In contrast to earlier studies on manufacturing industries, we find that legitimation effects are local and competition effects are global. This result points to the rapid turnover of ideas in fashion on the one hand and the global demand for fashion apparel on the other hand. We attribute the decline of Paris in the post-war period to 'institutional lock-in', which prevented a ready-to-wear cluster to emerge as vested interested of haute couture designers were threatened. An extended organizational ecology model provides empirical support for this claim.
Keywords: 330; Organizational ecology; fashion industry; creative industries; clusters; institutional lock-in; Mode; Bekleidungsindustrie; Wirtschaftskonzentration; Markteintritt; Organisatorischer Wandel; Bioökonomik; Welt